Civic Education for Muslim Students in the Era of Democracy Lessons Learned from Indonesia - Ubaedillah, Achmad (2018)
After the fall of the military regime in 1998, democracy has been the driving force for political and social changes in Indonesia. To nurture democracy as the public commitment within the nation, the role of Islamic higher education can be very critical in disseminating values and practices of democracy through a new civic education program for Muslim youth. Different from Indonesia's indoctrinated civic program in the past, the civic education introduced by State Islamic University Jakarta promotes a new approach and method of teaching democracy in such a new democratic country. The program contributes to democratic cultures and respect for Indonesian diversity.
Keywords: Indonesia; Islam; Muslim Students; Pancasila; Citizenship; Civic Education; Civil Society; Democracy